2014
DOI: 10.4103/1319-2442.128549
|View full text |Cite
|
Sign up to set email alerts
|

Renal allograft tuberculosis with infected lymphocele transmitted from the donor

Abstract: Transmission of tuberculosis (TB) from a donor through renal transplantation is a rare incident. We are reporting a 53-year-old Qatari woman diagnosed with renal allograft TB infection. The disease was confirmed by isolation of Mycobacterium tuberculosis from fluid from the lymphocele and demonstration of caseating granuloma in graft biopsy with acid-fast bacilli seen on Ziehl-Neelsen staining. The diagnosis was made quite early post-transplantation. The presence of the granuloma, which is unusual with patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Twenty‐three cases of donor‐derived TB (DDTB) were identified (Table ) . Thirteen (56.52%) were proven by molecular analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐three cases of donor‐derived TB (DDTB) were identified (Table ) . Thirteen (56.52%) were proven by molecular analysis.…”
Section: Resultsmentioning
confidence: 99%
“…During the period from 1998 to 2016, a total of 187 studies reported 2082 cases of TB after SOT . The majority (135/187 [72.19%]) were case reports or series, while the remainder were retrospective studies (n = 43),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through December 2016, a total of 22 case reports, 2 case series and 1 cohort reported on 36 cases of proven (n = 17), probable (n = 8), and possible (n = 11) DDTB cases among 16 lung, 13 kidney, 6 liver, and 1 heart recipient.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the median duration of treatment was 10.5 (range, 6-24) months (Table 3). Among those who completed treatment, the length of therapy for liver, kidney, and lung recipients was a median of 9 (range, 6-18), 12 (range, [9][10][11][12][13][14][15][16][17][18], and 18 months (range, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] respectively. All-cause mortality was 9/36 (25%), with TB-attributable mortality of 44% (4/9).…”
Section: Treatment and Outcomementioning
confidence: 99%